MODEL DEVELOPMENT OF CONTINUANCE INTENTION IN USAGE OF MOBILE COMMERCE APPLICATION BY CONSIDERING USABILITY SYSTEM - ODILIA SUMANTRI, CYNDI
M-commerce applications has been growing rapidly in the recent years. This is caused by the smartphones proliferated and the highspeed mobile data networks (internet) become increasingly ubiquitous. However, the level of users conducting transactions through m-commerce is still quite low, one of the reasons is that users do not fully understand about the usability of m-commerce services. In the context of mobile applications, usability is the quality of application design that facilitates interaction between users and its applications in achieving certain goals. Therefore, this study aims to describe the usability by some factors and determine the effect of usability on the continuance intention of using m-commerce application through the three-dimensional stage of human behavior (cognitive, affective, conative). This study uses 565 user data of m-commerce applications in Indonesia which collected through an online questionnaire survey. Data processing is performed by Structural Equation Modeling (SEM) which consists of two stage of tests, namely measurement model test and structural model test. Then, the Multigroup SEM method is used to access differences between groups of users with high and low experience and between groups of users with high and low frequency. The results showed that the seven dimensions of usability; accuracy, aesthetics, efficiency, interactivity, interface structure, learnability, and utility can describe the concept of usability well. Usability is proven to have a direct and significant positive effect on the continuance intentions. Then, it was found that m-app engagement has a full mediating effect on the relationship of trust towards continuance intentions and the relationship of enjoyment on continuance intentions. In addition, there were some differences found in the relationship between the high and low experience groups and also between the high and low frequency groups